HISTOPATHOLOGICAL OVERVIEW ASIAN REDTAIL CATFISH (Hemibagrus nemurus) SKIN AND GILLS INFECTED WITH ECTOPARASITES - Hanifah, Nada; Hidayati, Sri; Aji, Muhammad Tri (Asian Journal of Aquatic Sciences, 2024)
Frequent problems faced in fish farming are possible parasites that cause a declining level of fish production. The study's objective is to know the damage to the skin and gills of Asian redtail catfish in a manner that infects histopathology ectoparasites. The sample used three fish in each pool: Freshwater Fish Hatchery and Cultivation (PBIAT) Ngrajek and Regional Technical Implementation Unit (UPTD) Freshwater Fish Hatchery Sawangan in July 2022. Results data analysis inspection histopathology skin found necrosis and infiltration cell inflammation, for gill found exists infection parasite Dactylogyrus sp and Ichthyophthirius multifiliis as well as secondary lamellae adhesions, congestion, and cartilage hyperplasia hyaline.